Bio-banding in judo: The mediation role of anthropometric variables on the maturation - Giudicelli, B. B.; Luz, L. G. O.; Sogut, M.; Massart, A. G.; Júnior, A. C.; Figueiredo, A. J. (International Journal of Environmental Research and Public Health, 2020)
Young judo athletes are bio-banding based on age and body mass and compete in weight classes. The purposes of this study were to investigate the influences of maturation on physical performance in young judokas through controlling the chronological age and body mass, and to examine the mediating role of anthropometric variables. Sixty-seven judokas, aged 11.0-14.7, were measured for 11 anthropometric and seven physical performance variables. Pearson partial correlations were conducted to verify the relationship between the maturational indicator and the dependent variables. Mediation analyses were performed to identify the extent to which anthropometric variables mediate the relationship. The maturation e ect remained on the aerobic capacity and handgrip strength (p < 0.05). Fat mass (b = 80.335, 95%CI 11.580-204.270) and fat-free mass (b = 108.256, 95%CI 39.508-207.606) totally mediated the e ect on aerobic capacity. Fat mass (b = 0.023, 95%CI 0.004-0.057), fat-free mass (b = 0.029, 95%CI 0.011-0.058), stature (b = 0.031, 95%CI 0.008-0.061), arm span (b = 0.021, 95%CI 0.003-0.044), and inferior members length (b = 0.022, 95%CI 0.005-0.049) totally mediated the e ect on handgrip strength. The e ect of biological maturation is noticeable even after age and body mass control, being mediated by anthropometric variables related to body composition and size.